Enhanced-AAWP,a heterogeneous network oriented worm propagation model - LIU Bo; WANG Huai-min; XIAO Feng-tao; CHEN Xin (Tongxin xuebao)
A logical worm propagation model contributes to the analysis of how exactly various worms spread in Internet.With the abstract of heterogeneous network environments,and considering the impact of infection time on worm propa-gation,a heterogeneous network oriented worm propagation model namely Enhanced-AAWP was derived using discrete time and deterministic approximation.Then,the worms which employed local preference scanning or random scanning were studied based on Enhanced-AAWP.As the simulation results show,the amount of NAT,the density of vulnerable hosts in NATs,and the probability of local preference scanning are influencing factors during the course of worm propa-gations in heterogeneous network environments.